MEMBANGUN LINGKUNGAN SOSIAL ANTI-BULLYING MELALUI NILAI-NILAI HADIS - Khairul Kahfi; Muhammad Alif (Adisam Publisher, 2026)
This study aims to examine hadith themes relevant to the prevention and mitigation of bullying from an Islamic perspective. The research employs a thematic hadith (mawḍū‘ī) method with a qualitative approach by tracing hadiths that share a unified objective (wihdah al-ghāyah) related to the prohibition and prevention of bullying. The search was conducted in major hadith collections using the keywords “anti-bullying,” “prohibition of bullying,” and “bullying prevention,” resulting in 15 hadiths selected as research samples. These hadiths were then classified into four main themes: fundamental principles of the prohibition of bullying, verbal bullying and communication ethics, physical bullying and behavioral self-control, and positive moral values as a means of bullying prevention. The findings indicate that the hadiths of the Prophet Muhammad (peace be upon him) provide a comprehensive ethical and moral framework that rejects all forms of behavior that harm others, whether physically, verbally, or psychologically. The prohibition of hatred, envy, and violence, along with the command to guard one’s speech and control emotions, affirms that bullying contradicts the objectives of Islamic law, which uphold human dignity and social welfare. Furthermore, the cultivation of positive moral values such as iḥsān (benevolence), gentleness, empathy, and compassion is viewed as an effective preventive strategy for fostering a harmonious social environment free from bullying practices. This study concludes that hadiths function not only as normative prohibitions but also as moral guidance for character formation and the development of a civilized and ethical social order.